World Christian encyclopedia - Johnson, Todd M. 1958-; Zurlo, Gina A. (Edinburgh Edinburgh University Press, 2020)
The World Christian Encyclopedia, now in its 3rd edition, documents the changing status of World Christianity over the past 120 years from historical and social scientific perspectives. It records the continued shift of Christianity to the Global South and contains estimates for religious and nonreligious affiliation in every country of the world, including detail on Christianity to the denominational level. This reference work features comprehensive descriptions of all Christian traditions, including current information on the uniqueness of Christian experiences around the world
Literaturangaben
Keywords: Christianity; Christian Sects; Ecclesiastical geography; Demography -- Religious aspects; Christianity -- Statistics; Christian Sects; Christianity; Ecclesiastical geography; Statistics; Encyclopedias; Encyclopedias; Enzyklopädie